Early Hip Dislocation Rate in a Consecutive Series of 1093 Primary Total Hip Arthroplasties Using Imageless Navigation - Chuvanichanon, Pattawat; Suksathien, Yingyong; Seuajui, Jithayuth; Tippimanchai, Thanut; Khamphaeng, Sirawitz (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: Postoperative hip dislocation remains a major complication in total hip arthroplasty. Various studies have demonstrated that several factors influence dislocation. While computer-assisted navigation has been proposed to enhance component alignment, its impact on dislocation rates remains unclear. This study aimed to investigate the early dislocation incidence and associated risk factors in primary total hip arthroplasty (THA) using imageless navigation. Methods: A retrospective review of patients undergoing imageless-navigated THA between February 2013 and December 2022 was conducted. Inclusion criteria comprised primary THA with a minimum 6-month follow-up. Statistical analysis included univariate regression to identify dislocation risk factors. Results: A total of 1093 THAs were analyzed. Dislocation occurred in 16 cases (1.5%), six in elective procedures (0.76%), and 10 in femoral neck fracture (FNF) (3.28%). The univariate regression analysis revealed that FNF emerged as a significant risk factor (OR = 4.418, P = 0.004), while age, gender, femoral head size, and save zone cup placement of Lewinnek did not significantly affect dislocation rates. Conclusions: Navigation use showed a reduced rate of early dislocation. FNF is a factor associated with postoperative hip dislocation in primary THA.